Svāmī Vivekānanda : pañcāṅkī gadya nāṭaka - Kolhaṭakara, Acyuta Balavanta, 1879-1931 (SAMP early 20th-century Indian books project, 1914)
Play based on the life of Swami Vivekananda, 1863-1902, Hindu religious leader.